Strategi Pola Komunikasi Organisasi Dan Pengelolaan Informasi Digital Melalui Saluran Media Sosial Guna Meningkatkan Efesiensi Dalam Berkomunikasi - Aldo Alizamardi; Muhammad Zaikal Alfarizi; Aditya Rizki Al Fakhri; Ahmad Rafii Am (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2025)
This study examines the transformation of organizational communication patterns from a conventional bureaucratic model to a social media-based digital system to improve operational efficiency. Integrating Joseph A. Devito's communication pattern theory and Littlejohn & Foss's organizational dimensions, this study analyzes the effectiveness of the "All-Channel" communication pattern in mitigating communication barriers. Through case studies of the Jakarta Provincial Government and Tokopedia, it was found that two-way symmetrical communication significantly accelerated information distribution and reduced coordination costs. However, this efficiency requires structured information governance through content validation and digital standard operating procedures (SOPs) to address the risk of information overload. This study concludes that the key to successful modern organizational communication lies in the synergy between social media adoption, systematic information management, and strengthening member digital literacy.